Oküler Tüberküloz II: Tanı ve Tedavi - (:unkn) unknown (My University, 2011)
Son dönemlerde tüberkülin deri testi (TDT), interferon gama salınım analizleri (IGRA), toraksın bilgisayarlı tomografisi ve polimeraz zincir reaksiyonu ile ilgili yapılmış çalışmalar oküler tüberküloz (TBC) tanısının konulmasında yeni yaklaşımların doğmasına neden olmuştur. Ancak, TDT ve IGRA latent TBC enfeksiyonunun ortaya konmasında yardımcıdır ve aktif enfeksiyonu ayırt ettirmez. ıntraoküler TBC tanısını destekleyici diğer bir test ise akciğerin grafi veya bilgisayarlı tomografi yolu ile görüntülemesidir. Tanı için do¤rudan kanıt oluşturan testler aside rezistan boyama/sürüntü, oküler doku/sıvıların Mycobacterium tuberculosis kültürü ve nükleik asit amplifikasyon analizleridir. Son dönemde, intraoküler TBC için tanısal kriterler de tanımlanmışltır. Günümüzde intraoküler TBC için önerilen tedavi protokolü izoniazid, rifampisin, etambütol ve pirazinamid ile dörtlü tedavinin uzun süreli (toplam 9-15 ay) kullanımından oluşmaktad›r. (Turk J Ophthalmol 2011; 41: 182-90)

Recent studies on the clinical importance of tuberculin skin tests (TST), interferon-gamma release assays (IGRAs), chest computed tomography (CT) and polymerase chain reaction have provided a new approach to diagnosing ocular tuberculosis (TBC). However, both TST and IGRAs cannot distinguish between latent TBC infection and active disease. Another corroborative test in the diagnosis of intraocular TBC is the evaluation of the lungs by either chest radiography or CT. Direct evidence for the diagnosis can be obtained by examination of smears and staining for acid-fast organisms, cultures of intraocular tissue/fluid for Mycobacterium tuberculosis, and nucleic acid amplification analysis. In recent years, guidelines have been suggested for the diagnosis of intraocular TBC. The current treatment of intraocular TBC consists of use of four drugs (isoniazid, rifampicin, ethambutol and pyrazinamide) taken for a long period of time (total 9-15 months). (Turk J Ophthalmol 2011; 41: 182-90)
Ocular Tuberculosis II: Diagnosis and Treatment
Keywords: Göz Hastalıkları